You're A Big Bear Now, Winston Brown! - May, Paul; Illustrated by Young, Selina (New York Dorling Kindersley Publishing, 2001)
His parents keep forgetting that Winston is a big bear now, but when he discovers a burglar in the house who has eaten all of his porridge, Winston proves that he is both big and brave. Includes suggested activities.
Include Color Illustrations
Keywords: Bears -- Courage -- Growth